2010
DOI: 10.1016/j.tem.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y and sex hormone interactions in humoral and neuronal regulation of bone and fat

Abstract: The hypothalamus regulates the skeleton and adipose tissue via endocrine mechanisms. Changes in sex steroid levels in menopause and aging are central to the associated changes in bone mass and adiposity. Whereas many of these effects occur via direct actions on osteoblasts or adipocytes, sex hormones can also mediate effects on bone and adipose tissue via interaction with neuronal pathways. A key hypothalamic regulator of bone and adipose tissue is neuropeptide Y (NPY), which coordinately influences these tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 110 publications
1
21
0
Order By: Relevance
“…Thus, hyperprolactinemia may be an additional factor required for bone loss during lactation. Finally, it has become increasingly clear that bone cell behavior can be regulated by direct neural input from the hypothalamus (61)(62)(63). In this regard, it is interesting to note that suckling stimulates the production of neuropeptide Y (NPY) in the hypothalamus and that NPY contributes to alterations in feeding behavior and GnRH secretion during lactation (15,64,65).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hyperprolactinemia may be an additional factor required for bone loss during lactation. Finally, it has become increasingly clear that bone cell behavior can be regulated by direct neural input from the hypothalamus (61)(62)(63). In this regard, it is interesting to note that suckling stimulates the production of neuropeptide Y (NPY) in the hypothalamus and that NPY contributes to alterations in feeding behavior and GnRH secretion during lactation (15,64,65).…”
Section: Discussionmentioning
confidence: 99%
“…NPY is a potential modulator of bone remodeling. It exerts hypothalamic actions on the bone and adipose tissues and locally affects osteoblasts and adipocytes (Karsenty, 2000;Zengin et al, 2010). Recent studies have demonstrated NPY expression in osteocytes and an inhibitory effect of NPY on the osteoblast activity Paic et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A direct role has been described in the recent years for cannabinoid receptors (G-protein-coupled receptor superfamily) in the prevention of age-related osteoporosis using a knockout mouse for the cannabinoid receptor (CB1 −/− mice) [45]. Interactions between the neuromodulator, neuropeptide Y, and sex hormones in the regulation of bone and fat have also now been suggested based on a body of work with genetically modified mouse models for neuromodulatory agents and estrogen receptors [46]. It will be interesting to see how this translates into the "switch" between bone and fat cells in the aging marrow [46].…”
Section: Growth Factors Neuromodulators and Inflammatory Cytokines mentioning
confidence: 99%
“…Interactions between the neuromodulator, neuropeptide Y, and sex hormones in the regulation of bone and fat have also now been suggested based on a body of work with genetically modified mouse models for neuromodulatory agents and estrogen receptors [46]. It will be interesting to see how this translates into the "switch" between bone and fat cells in the aging marrow [46]. Recently, a hitherto unrecognized protein known to be involved in neuronal cell migration and development has also been shown to display bone effects [47•].…”
Section: Growth Factors Neuromodulators and Inflammatory Cytokines mentioning
confidence: 99%